Efektivitas Pembelajaran Jarak Jauh pada Mata Kuliah Survei dan Pemetaan Sumberdaya Wilayah di Masa Pandemi Coronavirus Disease 2019 - Yunus Aris Wibowo; Lintang Ronggowulan; Zaenal Abidin; Arief Cahyo Utomo; Eka Wulan Safriani; Yunita Miftakhunisa (Universitas Muhammadiyah Surakarta, 2020)
The COVID-19 pandemic has a negative impact on the education sector. The learning process must be carried out remotely (Distance Learning), so it requires adjustments both by educators and students to run an effective learning. The purpose of this study was to analyze the effectiveness of Distance Learning using LMS Schoology, Youtube, and Google Meets in the Survey and Mapping of Regional Resources Course. This study used a quantitative approach with a pre-experimental design in which students were given a pretest and posttest. The pretest and posttest scores were analyzed using Normalized-Gain (N-Gain) to determine the effectiveness of Distance Learning using LMS Schoology, Youtube and Google Meets. The results of the analysis will be categorized as effective if there is an increase score at posttest compared to pretest. The results of this study indicated that Distance Learning using LMS Schoology, Youtube, and Google Meets was effective for the Survey and Mapping of Regional Resources Course with an average gain by 0.19 and an increase of posttest score by 3.56. This Research is expected to provide a perspective on learning strategies during a pandemic.Keywords: COVID-19, Distance Learning, Education, Geography, Learning Strategy